The legal system for the implementation of international commercial arbitration provisions in Algerian legislation - Nassima, CHIKH (International Journal of Psychosocial Rehabilitation, 2022)
Arbitration is one of the means of settling disputes amicably, especially in the field of international trade, and resorting to it achieves justice with easier and faster procedures for the benefit of the parties. The implementation of the arbitral award is one of the most important stages of the arbitration system, as it represents its result and the goal of its approval.The arbitrator’s ruling and the issue of its implementation is one of the most important topics of international commercial arbitration because the implementation of the arbitrator’s ruling represents the basis of the arbitration system itself, and this ruling enjoys the status of binding by virtue of the litigants’ agreement on it, so their implementation of the ruling is optional, and it may be compulsory in the event that the convict refuses to implement it by force.The international commercial arbitration award is not implemented in Algeria unless it fulfills certain conditions stipulated by the legislator in the Code of Civil and Administrative Procedures.Accordingly, we pose the following problem: How is the implementation of the international commercial arbitration award in Algeria?